Minimal residual disease assessment in B-cell precursor acute lymphoblastic leukemia by semi-automated identification of normal hematopoietic cells: A EuroFlow study - Verbeek, Martijn W C; Rodríguez, Beatriz Soriano; Sedek, Lukasz; Laqua, Anna; Buracchi, Chiara; Buysse, Malicorne; Reiterová, Michaela; Oliveira, Elen; Morf, Daniela; Oude Alink, Sjoerd R; Barrena, Susana; Kohlscheen, Saskia; et al. (Cytometry. Part B, Clinical cytometry, 2024)
Presence of minimal residual disease (MRD), detected by flow cytometry, is an important prognostic biomarker in the management of B-cell precursor acute lymphoblastic leukemia (BCP-ALL). However, data-analysis remains mainly expert-dependent. In this study, we designed and validated an Automated Gating & Identification (AGI) tool for MRD analysis in BCP-ALL patients using the two tubes of the EuroFlow 8-color MRD panel. The accuracy, repeatability, and reproducibility of the AGI tool was validated in a multicenter study using bone marrow follow-up samples from 174 BCP-ALL patients, stained with the EuroFlow BCP-ALL MRD panel. In these patients, MRD was assessed both by manual analysis and by AGI tool supported analysis. Comparison of MRD levels obtained between both approaches showed a concordance rate of 83%, with comparable concordances between MRD tubes (tube 1, 2 or both), treatment received (chemotherapy versus targeted therapy) and flow cytometers (FACSCanto versus FACSLyric). After review of discordant cases by additional experts, the concordance increased to 97%. Furthermore, the AGI tool showed excellent intra-expert concordance (100%) and good inter-expert concordance (90%). In addition to MRD levels, also percentages of normal cell populations showed excellent concordance between manual and AGI tool analysis. We conclude that the AGI tool may facilitate MRD analysis using the EuroFlow BCP-ALL MRD protocol and will contribute to a more standardized and objective MRD assessment. However, appropriate training is required for the correct analysis of MRD data.
Keywords: senioři; database; Reproducibility of Results; BCP‐ALL; reziduální nádor; Immunophenotyping; průtoková cytometrie; imunofenotypizace; pre-B-buněčná leukemie; reprodukovatelnost výsledků; B‐cell differentiation; kojenec; mladiství; hematopoéza; Middle Aged; Neoplasm, Residual; mužské pohlaví; Infant; Adult; mladý dospělý; dítě; automation; Child; Flow Cytometry; Automation; Child, Preschool; Young Adult; ženské pohlaví; Humans; předškolní dítě; lidé středního věku; Precursor B-Cell Lymphoblastic Leukemia-Lymphoma; automatizace; Hematopoiesis; dospělí; Female; Aged; Adolescent; MRD; lidé; Male